2020
DOI: 10.3390/ijerph17082813
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Housing Features and Environmental Factors on Home Indoor Radon Concentration Levels on the Navajo Nation

Abstract: Uranium is naturally found in the environment as a radioactive metal element with high concentrations in the Southwestern US. In this region is the Navajo Nation, which spans approximately 69,930 square kilometers. A decay product of uranium is radon gas, a lung carcinogen that has no color, odor, or taste. Radon gas may pass from soil into homes; and, indoor accumulation has been associated with geographical location, seasonality, home construction materials, and home ventilation. A home and indoor radon surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The non-uniform distribution observed within the study locality can be attributed to varying radium concentrations across all dwelling locations [ 3 , 8 ]. The measured radon concentration within the Kpando district, in 120 different dwellings, is presented in the form of a range, mean, median, mode, etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-uniform distribution observed within the study locality can be attributed to varying radium concentrations across all dwelling locations [ 3 , 8 ]. The measured radon concentration within the Kpando district, in 120 different dwellings, is presented in the form of a range, mean, median, mode, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Radon is classified as the second main cause of lung cancer after cigarette smoking. It has been characterized as cancerogenic and causes between 3 to 14% of all lung cancer cases reported globally [2][3][4][5]. Literature studies and the International Organization on Radiation Protection have reported that exposure to elevated indoor radon levels in enclosed areas such as dwellings can result in a higher risk of lung cancer incidence among the populace [2,6].…”
Section: Introductionmentioning
confidence: 99%
“…Barros-Dios et al [ 34 ] found older homes were primarily constructed of stone in both the exterior and interior of the home and they had significantly higher indoor radon levels, followed by stone-and-brick, and brick alone. Yazzie et al [ 35 ] found that homes constructed of cement and wood and homes constructed of concrete and cement had higher mean indoor radon concentrations than mobile homes and those constructed of wood and cement and wood alone. We need further study to examine the association of home building materials, age of home, and indoor radon levels.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of residential radon, the overall difference in burden of lung cancer between China and the world increased. In 2019, the Chinese age-standardized mortality and DALYs rates were about 40% higher than the global rates, which may be related to the changes in living and working styles, building types, construction and decorative materials, furniture, and fuel types in recent years 8,32 .…”
Section: Figurementioning
confidence: 99%